Symptoms of uterine myomas: data of an epidemiological study in Germany - Foth, Dolores; Rabe, Thomas (Archives of gynecology and obstetrics, 2017)
PurposeCurrently, no reliable data are available concerning the type and frequency of symptoms in premenopausal women with uterine myomas.Methods2296 women were examined by means of vaginal ultrasound for the presence of myomas in seven gynaecological outpatient departments in Germany. From this population, 1314 premenopausal women between the ages of 30 and 55 years were evaluated to determine the type and frequency of myoma-related symptoms and their relationship to anamnestic factors, and the number, size, and location of the myomas. Standardised questionnaires were used to record the symptoms.Results Prevalence: In almost every second premenopausal woman (n = 639; 48.6%), uterine myomas were diagnosed. The frequency of myomas increased continuously with age and was highest in women between 46 and 50 years (65.2%). Age itself was found to be the main risk factor for the presence of myomas (p < 0.001). Symptoms: 54.3% (n = 347) of the women suffered from myoma-related symptoms. The four main symptoms were identified as: Heavy menstrual bleeding (40.7%), dysmenorrhoea (28.2%), lower abdominal pain (14.9%), and intermenstrual bleeding (14.1%). In the majority of cases, the symptoms occurred simultaneously. Determinants for symptoms: Symptoms did not follow a clear age-related trend, whilst the number and size of the myomas did determine the presence of symptoms. The main influencing factor for the presence of intermenstrual bleeding was the location of the myomas.ConclusionsThe high prevalence of uterine myomas highlights the importance of the diagnosis uterine myomas in standard gynaecological practice: The presence of only one myoma caused symptoms in 46.5% and small myomas of up to 2 cm in diameter resulted in symptoms in 39.5%.